Devil's tower [large type] - Dundee, Wayne D. (Dundee, Wayne D. Lone McGantry, 2024)
"Bitter and heartbroken after the untimely death of a loved one, Lone McGantry finds himself once again aimlessly drifting across the frontier. Seeking solace from the woman who helped raise him, he visits "Ma" Sharples in North Platte, Nebraska, where he discovers Ma has been recently jilted of her life savings by conman Jack Swain. Feeling a renewed sense of purpose, Lone vows to track down the varmint. The trail takes many twists and turns, ultimately leading him to the violent Eccles gang. Lone makes this gang his new target, and is joined by a black U.S. Marshal, as well as a gunslinging gambler and his mistress who have their own grievances with Eccles' bunch. More danger is encountered before the gang is cornered against the looming butte known as Devil's Tower, where they are obsessed with uncovering a cursed ancient treasure."--